Blockchain Technology As A Tool For Supply Chain Transparency In The Fashion Industry: Aligning With SDGs And ESG Goals - Haque, Md Aminul (Digital Repository of Theses, 2025)
This study explored the potential impact of blockchain technology in enhancing supply chain transparency and sustainability in the fashion industry, particularly in relation to its alignment with the Sustainable Development Goals (SDGs) and the Environmental, Social, and Governance (ESG) principles. In this respect, a mixed-methods approach was chosen, including a quantitative survey among 269 professionals working within fashion supply chains and qualitative expert interviews with representatives of brands, technology providers, and policy organizations. Descriptive studies, reliability tests, correlational questions, and regression modelling were used to analyze quantitative data. The findings indicated the large internal consistency among all of the constructs of blockchain capability. Blockchain Data Immutability (BDI) and Stakeholder Data Accessibility (SDA) emerged as the main predictors of perceived supply chain transparency. The thematic analysis of qualitative results indicated that mechanizations of trust establishment, regulatory compliance requirements, and multi-tier supply chain visibility represented some of the key drivers of adoption, technological adequacy, economics, and resistance among upstream suppliers, and key adoption barriers. Even though blockchain is viewed as a provider of significant effects on traceability, real-time monitoring of compliance, and access to ESG data, the analysis showed that the current adoption is often confined to token projects or pilot programs. Full-scale diffusion is held back by the organizational inertia that persists in some organizations, digital illiteracy, and inefficient organizational governance structures. The findings were explained in the institutional category based on institutional theory and the resource-based view (RBV), which states the role of blockchain as a reaction to external forces and a possible strategic utility. At the same time, the Digital Product Passport (DPP) project offered by the European Union was also discussed critically as a regulation-driven alternative. Although DPP is a standardized method of sustainability reporting, the study found that it cannot offer the decentralized data verifiability that blockchain does, which increases concerns of data credibility and the empowerment of stakeholders. Adding empirical evidence of blockchain's operational and strategic implications in the context of fashion supply chains, the study also identified discrepancies between aspired potential and practices. The recommendations quoted the necessity of inclusivity of stakeholders, standardization of regulations, and governance based on ethics as the means to unlock the transformative potential of blockchain. The research aims to illuminate policymakers who can facilitate the adoption of scalable and sustainable blockchain solutions within the global fashion economy.